INTRODUCTION TO THE QURANIC METHOD AND STYLE IN THE VERSES OF THE COMMANDMENTS - Hafiz Zulqarnain; Muhammad Akmal (Journal of Religion and Society, 2025)
In this universe, just as Allah Almighty has provided every individual with the necessary provisions according to the demands of time, He has also taken care of their spiritual needs. To safeguard their spirituality, Allah Almighty has revealed various commandments. Among all the sciences of the Qur'an, the highest knowledge is that related to divine commandments, because through this knowledge, a person recognizes Allah's commands and acts upon them. There is a deep and strong connection between Qur'anic commandments, benefits, and wisdom. The reason for this is that all these commandments have been revealed by Allah Almighty, and Allah's actions are never devoid of wisdom and benefit. Just as Allah has created plants that contain cures for numerous diseases and innumerable benefits, similarly, His revealed commandments contain hidden and limitless benefits for humanity. In the modern era, every progressive individual’s heart is not only inclined towards seeking evidence for everything, but along with the evidence, they also desire to understand the wisdom and benefit behind it. If they perceive wisdom and benefit in something, they accept it without hesitation. However, if they find no wisdom or benefit in something, even if overwhelming evidence is presented, they will not be inclined to accept it. In conclusion, in the present age, two factors are crucial for the audience: one is evidence and the other is wisdom. Keywords: Qur'anic, Commandments, Spirituality, Progressive, Audience, Evidence, Wisdom.